Longitudinal Pathways to Reading Achievement at Age 7 Years: Child and Environmental Influences. Issue 3 (3rd April 2019) - Auerbach, Judith G.; Zilberman-Hayun, Yael; Berger, Andrea; Atzaba-Poria, Naama
Abstract : Using a bioecological perspective, this longitudinal study examined the contribution of child and environmental factors to the prediction of reading achievement at age 7. Participants were 99 boys and their parents. Child factors included 24-month temperament (reactivity and self-regulation), 36-month language level, and 7-year ADHD symptoms; environmental factors included quality of the home environment (54 months), maternal education, and learning disability (LD) in the family. There were direct and indirect pathways to reading achievement. Direct pathways included language skills, home environment, ADHD symptoms, and LD in the family. Unexpectedly, the direct pathway from self-regulation was negative. Indirect pathways included self-regulation, maternal education, and reactivity. Given the stability of the trajectory of reading skills and academic performance from first grade onward, the early identification of those children most at risk for reading difficulties has implications for the type of intervention most appropriate for individual children.